Karyotype Analysis of Diploid and Spontaneously Occurring Tetraploid Blood Orange [Citrus sinensis (L.) Osbeck] Using Multicolor FISH With Repetitive DNA Sequences as Probes - Deng, Honghong; Cai, Zexi; Xiang, Suqiong; Guo, Qigao; Huang, Wei; Liang, Guolu (Frontiers in Plant Science, 2019)
Blood orange (Citrus sinensis (L.) Osbeck) has been increasingly appreciated by consumers worldwide owing to its brilliant red color, abundant anthocyanin and other health-promoting compounds. However, there is still relatively little known about its cytogenetic characteristics, probably because of the small size and similar morphology of metaphase chromosomes and the paucity of chromosomal landmarks. In our previous study, a naturally occurring tetraploid blood orange plant was obtained via seedling screening. Before this tetraploid germplasm can be manipulated into a citrus triploid seedless breeding program, it is of great importance to determine its chromosome characterization and composition. In the present study, an integrated karyotype of blood orange was constructed using sequential multicolor fluorescence in situ hybridization (FISH) with four satellite repeats, two ribosomal DNAs (rDNAs), a centromere-like repeat and an oligonucleotide of telomere repeat (TTTAGGG)3 as probes. Satellite repeats were preferentially located at the terminal regions of the chromosomes of blood orange. Individual somatic chromosome pairs of blood orange were unambiguously identified by repetitive DNA-based multicolor FISH. These probes proved to be effective chromosomal landmarks. The karyotype was formulated as 2n=2x=18=16m+2sm (1sat) with the karyotype asymmetry degree belonging to 2B. The chromosomal distribution pattern of these repetitive DNAs in this spontaneously occurring tetraploid was identical to that of the diploid, but the tetraploid carried twice the number of hybridization sites as the diploid, indicating a possible pathway involving the spontaneous duplication of chromosome sets in nucellar cells. Our work may facilitate the molecular cytogenetic study of blood orange and provide chromosomal characterization for the future utilization of this tetraploid germplasm in the service of seedless breeding programs.